Q-switched vortex laser using a Sagnac interferometer as an output coupler - Geberbauer,JWT; Kerridge-Johns,WR; Damzen,MJ (SPIE-INT SOC OPTICAL ENGINEERING, 2020)
Vortex lasers are an attractive prospect for efficient generation of high-quality beams in compact, environmentally robust, and turnkey systems. We demonstrate conversion of a Q-switched, diode-pumped Nd:YVO4, TEM00 Gaussian laser into a vortex laser source by replacing the output coupling mirror by a vortex output coupler (VOC) based on an imbalanced Sagnac interferometer. The Q-switched VOC laser generated a vortex output with 5.1 W average power, slope efficiency of 46% at 150 kHz pulse repetition rate, only marginally lower than the 5.4 W and 49% slope efficiency of the plane mirror laser. Vortex handedness was switchable with a single VOC control without loss of vortex power. In both handedness cases the vortex mode quality was assessed to be excellent by detailed analysis of vortex phase profile and propagation characteristics and comparison to an ideal vortex. The power scaling potential of the VOC was demonstrated in a higher power cavity, achieving a vortex output power of 14.3 W and a slope efficiency of 55%. Further investigation verified the ability for the VOC laser to self-mode-filter the intracavity mode, showing maintenance of high TEM00 quality even after introducing deliberate mode to pump size mismatch, when the equivalent plane mirror laser becomes multimode. This work highlights the potential of the VOC as a simple route to high powered structured light sources using just standard high-power handling mirror components and its self-mode-filtering property to compensate intra-cavity spatial mode degradation when power-scaling.